Application of various types of local microorganisms to the growth and production of two rice varieties. Issue 1 (October 2020) - Rafiuddin,; Mollah, A; Pratiwi, E
Abstract: An experiment was conducted to determine the effect of application of various types of local microorganisms (LM) to the growth and production of two rice ( Oryza sativa L.) varieties. The experiment was conducted in the form of a 2-factor factorial design trial in the Randomized Block Design (RBD). The first factor was the variety, namely: Variety Mira-1 and Diah Suci. The second factor was 6 types of LM, namely: LM of gamal leaf, LM of vegetable waste, LM of fruit waste, LM of banana suckers, LM of cow urine and a mixture of those five LM ingredients; Therefore, there were 12 treatment combinations. The results showed that the Diah Suci variety gave higher yields than the Mira-1 variety on plant height, panicle length, number of grains, percentage of grain filled per panicle, 1000 grain weight, and grain production per hectare (11.42 tons/ha) The application of a mixture of the five types of LM resulted in a shorter flowering age of 66.33 HST, and a shorter harvest age of 102.33 HST. There are no results that indicate interactions between varieties and types of LM.